2012
DOI: 10.1002/asia.201200556
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Reactor Wall in Hydrothermal Biomass Conversions

Abstract: The processing of renewable feedstocks to platform chemicals and, to a lesser degree, fuels is a key part of sustainable development. In particular, the combination of lignocellulosic biomass with hydrothermal upgrading (HTU), using high temperature and pressure water (HTPW), is experiencing a renaissance. One of the many steps in this complicated process is the in-situ hydrogenation of intermediate compounds. As formic acid and related low-molecular-weight oxygenates are among the species generated, it is con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 48 publications
2
6
0
Order By: Relevance
“…However, during these reductions neither iron-carbonyl nor iron-hydride signals were detected (irrespective of whether sulfuric or formic acid was used). Nonetheless, as was shown previously, [18] the formation of catalytically inactive iron salts (formate or sulfate) occurred (see the Supporting Information for time-resolved IR spectra). When analyzing the gaseous product(s) formed (both in the presence and absence of cyclohexanone), only hydrogen could be detected.…”
Section: Resultssupporting
confidence: 75%
See 2 more Smart Citations
“…However, during these reductions neither iron-carbonyl nor iron-hydride signals were detected (irrespective of whether sulfuric or formic acid was used). Nonetheless, as was shown previously, [18] the formation of catalytically inactive iron salts (formate or sulfate) occurred (see the Supporting Information for time-resolved IR spectra). When analyzing the gaseous product(s) formed (both in the presence and absence of cyclohexanone), only hydrogen could be detected.…”
Section: Resultssupporting
confidence: 75%
“…It should be noted that the present study is the companion piece to its predecessor, [18] in which it was demonstrated that under the conditions used for hydrothermal upgrading (HTU) of lignocelluosic biomass, the walls of typical stainless steel reactors are able to effect ketone reductions in the presence of formic acid, itself a product typically formed under the HTU conditions.…”
Section: Introductionmentioning
confidence: 77%
See 1 more Smart Citation
“…In these processes the stainless-steel reactor wall potentially acted as ac atalystf or the (de)hydrogenationsa nd hydrogenolyses. [23] Similarly,w hen vanillin was heated under neutral conditions only at race of guaiacol was generated. However,h eating under basic conditions generatedavariety of products,i nclud-ing guaiacol, catechol, and 4-methylguaiacol.…”
mentioning
confidence: 99%
“…On the other hand, high reactive oxygen species (ROS) can be generated by the Fenton‐like reaction between zero‐valent iron (ZVI) and O 2 or H 2 O 2 at room temperature . Besides, it is confirmed that the reactor wall of stainless steel has evident activity for catalytic hydrogenation using formic acid as hydrogen source . In a word, we speculate that the inconsistence in main products formed by this method is strongly affected by alkalinity of solution and reactor material.…”
Section: The Potential Strategies For Lignin Valorizationmentioning
confidence: 83%